Application of intelligent sorting of customer service work orders with multiple factors vectorization - Hua REN; Zheng WANG; Shaomin WANG (Dianxin kexue)
As the most important contact point for customers in the internet industry,customer service orders have become the main issues that need to be addressed and urgently solved in various industries.The intelligent sequencing of work orders provides a feasible application for solving this problem.The rapid development of artificial intelligence technology and big data technology has given new directions and opportunities to solve such problems.The background of the intelligent sequencing of customer service orders was analyzed firstly.On the basis of this,the main methods and implementations of intelligent sequencing of customer service orderswere analyzed,and the application of intelligent sequencing of customer service orders based on multi-factor vectorization was expounded.